THE IMPLEMENTATION OF ENGLISH LEARNING BASED ON MODEL OF INTERCULTURAL COMMUNICATIVE COMPETENCE (ICC) FOR IMPROVING STUDENTS’ COMMUNICATION INDEPENDENCE - Edi, Edi (English Review: Journal of English Education, 2022)
The purpose of this research is to determine the implementation of English learning based on the intercultural communicative competence (ICC) model to increase student independence in communication. Students can develop their talents, interests, knowledge, attitudes, awareness, behaviour, and skills when talking with people from different cultures (foreigners). The method approach in this research is qualitative-grounded theory using the techniques and data analysis of Miles and Huberman (1994), namely data collection, data reduction, data display, and conclusion drawing/verification. The number of participants in this research consisted of eleven participants in the fourth semester and eleven participants in the sixth semester, so total participants were twenty-two participants in this research, this sample was taken randomly. The results of this study show that students could not implement five dimensions, namely skills: interaction (11), knowledge: social (5), awareness: practice (5), attitude: 4 and behaviour: 3. Conclusion of this research, the students of the English Education Department, Faculty of Teacher Training and Education University of Muhammadiyah Mataram implemented three main dimensions encompasses skills: The ability to interact, knowledge: social knowledge, and awareness: awareness to do the practice.